Smart paper electronics by laser-induced graphene for biodegradable real-time food spoilage monitoring. (December 2022) - Jung, Yeongju; Min, JinKi; Choi, Joonhwa; Bang, Junhyuk; Jeong, Seongmin; Pyun, Kyung Rok; Ahn, Jiyong; Cho, Yeongtak; Hong, Seunghun; Hong, Sukjoon; Lee, Jinwoo; Ko, Seung Hwan
Highlights: Simple laser irradiation process could convert many kinds of commercial papers into laser-induced graphene (LIG) of highly porous 3D structure. LIG-based sensor on paper substrate is capable of monitoring the current freshness of food by detecting the gas emitted from the food. LIG sensor could detect food storage temperature that estimates the food quality in near future. LIG-based sensor could be in-situ directly fabricated on the commercial food package such as milk carton and paper cup. The smart wireless monitoring system informs the users of food quality via the mobile phone before food intake in daily life. Abstract: In situ monitoring system on the food package based on biodegradable materials to examine the food status is of great significance for practical application since food poisoning and non-degradable package waste have raised critical healthcare and environmental issues recently. Here, we report a laser-induced paper sensor (LIPS) that is comprised of a laser-induced graphene (LIG)/paper hybrid structure for wireless, real-time monitoring of the food status by the chemical- and thermo- sensing capabilities of LIPS. Direct laser irradiation on any type or structure of commercial paper converts the laser-irradiated paper surface into LIPS with a decent sheet resistance of 105 Ω sq −1 and porous structure which enables smart monitoring of key parameters such as gas concentration and temperature for the food spoilage prior to the food intake. Optimized laser irradiation conditions on the paper substrate produced the temperature and chemical gas coefficient of resistance change of 0.15%°C −1 and 0.0041% ppm −1 . As a proof-of-concept, we fabricated LIPS on the surface of the paper to both detect the temperature and monitor the chemical degradation of the food, of which data can be directly delivered to the user's mobile device through continuous wireless communication. We believe that LIPS proposed herein will make significant contributions to the next-generation food-related green electronics to provide users with a smart and high-fidelity monitoring platform for simple detection of the real-time status of food products. Graphical abstract: Paper electronics directly drawn on a paper cup, a milk carton and a meat price tag. Image, graphical abstract